Developing, Validating, and Applying a Measure of Human Quality Treatment - McGhee P; Haar J; Ogunyemi K; Grant P (Springer Nature B V, 2023)
Human Quality Treatment (HQT) is a theoretical approach expressing different ways of dealing with employees within an organization and is embedded in humanistic management tenants of dignity, care, and personal development, seeking to produce morally excellent employees. We build on the theoretical exposition and present a measure of HQT-Scale across several studies including cross-culturally to enhance confidence in our results. Our first study generates the 25 items for the HQT-Scale and provides initial support for the items. We then followed up with a large study of managers (n = 363) from Nigeria in study 2, which confirms the theoretical properties of the five dimensions of HQT and highlights a two-factor construct: HQT Ethically Unacceptable and HQT Ethically Acceptable using a 20-item HQT-Scale. Study 3 with a large sample of New Zealand employees (n = 452) again confirms the nature of the construct and provides construct validity tests. Finally, using time-lagged data, study 4 (n = 308) focuses on New Zealand employees and job attitudes and behaviors, and a well-being outcome. That study not only confirms the theoretically implied effects but also shows the HQT Ethically Acceptable factor mediates the detrimental effects of HQT Ethically Unacceptable. Overall, our four studies provide strong support for the HQT-Scale and highlight important understandings of HQT and humanistic management in the workplace.
Keywords: Human Quality Treatment; Humanistic management; Scale development; HQT-Scale; Employee attitudes, behaviors, and well-being